Optimal Reactive Power Dispatch for Voltage Stability Improvement Considering Line Contingencies using PSO - Nor Rul Hasma, Abdullah; I., Musirin (2013)
This paper presents a swarm intelligence algorithm for monitoring and improving voltage stability in power system considering a contingency conditions; line outage. The Static Voltage Stability Index(SVSI) was used as the monitoring tools and as the objective function for the developed optimization technique. This index uses information on a normal load flow and is in the range of 0 (zero load) to 1(system collapse). The proposed algorithm gives an optimal setting of control devices such as switchable VAR compensator and able to minimize total transmission losses, improved voltage stability and increase voltage profile of the system. The effectiveness of the proposed technique was validated on standard IEEE 30-bus Reliability Test System (RTS). The simulations results are compared with those obtained from the Evolutionary Programming (EP) technique in the attempt to highlight its merit.